Estudo in silico: otimização do potencial anticolinesterásico do ácido vanílico, com vistas ao uso na doença de Alzheimer, determinado por docking molecular - Barros, Kevin Christophe Peixoto Pereira (Brasil, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder and the leading cause of dementia and disability in the elderly. Despite extensive research, its complete pathophysiology remains elusive. Current pharmacological treatments primarily target the cholinergic hypothesis using acetylcholinesterase inhibitors (AChEIs) and NMDA receptor antagonists. Known for its rich content of anthocyanins and phenolic compounds, Thunbergia erecta has demonstrated potential AChE inhibitory activity, particularly with vanillic acid and apigenin. This study aims to evaluate the anticholinesterase activity of vanillic acid from T. erecta through in silico testing and propose structural optimizations using molecular modeling. An in silico screening was conducted using molecular docking techniques to evaluate the interactions between vanillic acid derivatives and AChE. The strategy of maintaining the hydroxyl-phenyl-carbonyl portion in the proposed structures proved effective, providing hydrogen bonding interactions. The addition of aromatic side chains favored π-π stacking interactions, and amine groups promoted π-alkyl interactions. Among the 12 proposed ligands, 6 were found to be promising, with compounds 5, 8, and 11 standing out.